Forgiveness, reconciliation and justice á la Desmond Tutu - P.G.J. Meiring (Acta Theologica)
In the eyes of many, chairing the South African Truth and Reconciliation Commission (TRC) was the crowning contribution of Archbishop Desmond Tutu to his country, and to the world at large. Against the backdrop of his role leading the TRC, chairing the many victims’ hearings and guiding the amnesty proceedings, the article focuses on Tutu’s views on forgiveness, reconciliation, and justice. The TRC operated within the mandates given to it by the South African parliament, but Tutu with his theological background, strong views, and dynamic personality put his own stamp on the truth and reconciliation process in South Africa. The role of religion in establishing truth and working towards justice, forgiveness, and reconciliation was controversial, but for the former Anglican Archbishop of Cape Town, it was inconceivable to embark on the journey of reconciliation without faith in Jesus Christ, the ultimate Reconciler.